MIDDLE TRIASSIC FORAMINIFERA FROM THE SECEDA CORE (DOLOMITES, NORTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
The assemblage of foraminifera in turbidite beds in Middle Triassic basinal deposits straddling the Anisian/Ladinian boundary interval was studied in 224 thin sections. The fauna consists mainly of shallow-water inhabitants, associated with calcareous hyaline foraminifera (Lagenina) of open marine environment. Due to a well established  biostratigraphy in the studied interval, the first and last appearance of some shallow water, benthic foraminifera can be assigned to the Mid Triassic ammonoid stratigraphy. The species Meandrospira dinarica Kochansky-Devidè & Pantic and Arenovidalina chialingchiagensis Ho are limited to the Reitzi ammonoid zone. The species Variostoma alta Kristan and Hoyenella gr. sinensis both do not superate the Curionii zone in age in the studied succession.  The biostratigraphic most important event occurs at the base of the Gredleri zone,  with the appearance of the family Involutinidae Bütschli, represented by the genera Lamelliconus and Aulotortus. The faunal composition is similar to those of neighbouring paleoprovinces, but generally a lower faunistical diversification compared to foraminiferal assemblages in the Anisian or Carnian is observed.